144k views
23 votes
Please help me on this one guys​

Please help me on this one guys​-example-1

2 Answers

9 votes
  • (6x² + 5x - 3) + (x² - 9)

Remove the brackets.

  • = 6x² + 5x - 3 + x² - 9

Take the like terms closer.

  • = 6x² + x² + 5x - 3 - 9

Now do the addition and subtraction

  • = 7x² + 5x - 12

Let us split the middle term

  • = 7x² + 12x - 7x - 12

Now take x as common from the first two terms and -1 from the next two terms.

  • = x (7x + 12) - 1 (7x + 12)
  • = (x - 1)(7x + 12)

Answer:

(x - 1)(7x + 12)

Hope you could understand.

If you have any query, feel free to ask.

User KickAss
by
5.1k points
1 vote

Question:-

Solve (6x² + 5x - 3) + (x² - 9)

Answer:-

(x-1) (7x+12)

Step-by-step explanation:-

please look at the attached picture :)

Please help me on this one guys​-example-1
User TeknasVaruas
by
5.0k points